Computers in Cardiology, 2005 2005
DOI: 10.1109/cic.2005.1588241
|View full text |Cite
|
Sign up to set email alerts
|

An on-line ischemia monitoring algorithm for mobile devices

Abstract: The early diagnosis of ischemic events may prevent irreversible damage to the heart muscle. Mobile IntroductionMyocardial ischemia is one of the diseases with highest incidence rate in the industrialised countries. Physiologically, is identified by an insufficient oxygenated blood supply compared to current myocardial demand. This event is reflected in a ECG signal as anomalous variations during the ventricular re-polarization. Although the ECG signal analysis is not the most accurate method that exists to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The use of the decision trees techniques rediscovered some of the rejection rules proposed in the previous paper [1], other ones reappeared more refined, new ones have been discovered and the new rejection module proved to be more accurate.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The use of the decision trees techniques rediscovered some of the rejection rules proposed in the previous paper [1], other ones reappeared more refined, new ones have been discovered and the new rejection module proved to be more accurate.…”
Section: Resultsmentioning
confidence: 95%
“…The detection algorithm is based on a previous own algorithm for real-time transient ST-segment episodes detection that was developed and validated over the freely available part of the LTST database [1]. In this work we improve this algorithm and incorporate to it a more sophisticated rejection module using techniques based on decision trees.…”
Section: Ischemia Detectionmentioning
confidence: 99%
“…Nevertheless, repetitive patterns suitable for real-time discrimination between ischemic and non-ischemic episodes have been noticed in Dranca et al (2005) and confirmed in Dranca et al (2006) by decision tree methods.…”
Section: Apply Discriminantmentioning
confidence: 99%
“…[10][11][12][13][14][15] A new device, the Spandan portable ECG device 12L is a portable ECG designed for quick access of 12 Lead ECG at homes and clinics has become available in the diagnostics market.…”
mentioning
confidence: 99%